2009
DOI: 10.1103/physrevb.79.209901
|View full text |Cite
|
Sign up to set email alerts
|

Publisher's Note: Modeling and analysis of the three-dimensional current density in sandwich-type single-carrier devices of disordered organic semiconductors [Phys. Rev. B79, 085203 (2009)]

Abstract: Modeling and analysis of the three-dimensional current density in sandwich-type single-carrier devices of disordered organic semiconductors Holst, J.J.M. van der; Uijttewaal, M.A.; Ramachandhran, B.; Coehoorn, R.; Bobbert, P.A.; de Wijs, G. A. ; Groot, R.A. de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 0 publications
2
75
0
Order By: Relevance
“…In these 3D device studies, 15 the current density was found to be highly inhomogeneous, in agreement with other studies. [16][17][18][19] This inhomogeneous structure involves narrow current filaments that carry almost all the current, characteristic of the percolative nature of charge transport in disordered materials.…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…In these 3D device studies, 15 the current density was found to be highly inhomogeneous, in agreement with other studies. [16][17][18][19] This inhomogeneous structure involves narrow current filaments that carry almost all the current, characteristic of the percolative nature of charge transport in disordered materials.…”
Section: Introductionsupporting
confidence: 79%
“…III we present the current-voltage characteristics of devices with uncorrelated as well as correlated disorder, corresponding to the EGDM and ECDM, respectively. For the case of the EGDM, we compare our results with our previous work based on the master-equation approach, 15 while for both the EGDM and the ECDM we compare our results with those of 1D drift-diffusion modeling. In Sec.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations